2022
DOI: 10.55006/biolsciences.2022.2401
|View full text |Cite
|
Sign up to set email alerts
|

Trachyspermum ammi: A review on traditional and modern pharmacological aspects Traditional and modern aspects

Abstract: Ajwain, dried mature seed like fruits are well known by names such as thymol seeds, caraway, carom, ajowan, or bishop's weed, belongs to the Apiaceae family. Carum copticum is the Latin name for this spice. Trachyspermum ammi (L.) Sprague ex Turrill is scientific name. This spice is indigenous to Egypt, although it is also cultivate in India, Iran, Pakistan, Iraq, Afganistan, other nations in South and West Asia as well as Europe. Gujarat and Rajasthan are Indian states noted for their ajwain cultivation. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Subsequently, 178 µl of EDC was added to the CHOL solution, and the mixture was kept in darkness for a short period. To the formation of amid linkages between the carboxyl groups of CHOL (C 26 H 45 COOH) and the amino groups of CS ( a [ 1 4 ]-2-amino-2-deoxy B -D-glucan), the CHOL-EDC mixture was added dropwise, slowly, to a solution containing 75 µl of CS while stirring on a magnetic stirrer. To ensure a complete formation of amid linkages between CS and CHOL, The resulting mixture was left to stir on a magnetic stirrer for 24 h to allow for adequate linkage formation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, 178 µl of EDC was added to the CHOL solution, and the mixture was kept in darkness for a short period. To the formation of amid linkages between the carboxyl groups of CHOL (C 26 H 45 COOH) and the amino groups of CS ( a [ 1 4 ]-2-amino-2-deoxy B -D-glucan), the CHOL-EDC mixture was added dropwise, slowly, to a solution containing 75 µl of CS while stirring on a magnetic stirrer. To ensure a complete formation of amid linkages between CS and CHOL, The resulting mixture was left to stir on a magnetic stirrer for 24 h to allow for adequate linkage formation.…”
Section: Methodsmentioning
confidence: 99%
“…In the end, two separate phases were created; the supernatant was discarded, and the sediment containing CS-CHOL Nano-gel encapsulated with T. ammi EO was used for microbial tests. The optical absorbance of the supernatant was taken by UV-Vis spectrophotometry using а Varioskan Flash Multimode Reader (Thermo Scientific, Waltham, MA) at a wavelength of 280 nm to calculate the Loading efficiency of the EO according to the formula [ 1 ]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnopharmacology of plants helps to identify natural plants with therapeutic potential in specific ethnic or cultural regions. For example, Trachyspermum ammi (L.) Sprague ex Turrill or Carom seeds or Ajwain are cultivated in subcontinent regions and are commonly used in the treatment of digestive disorders in humans and animals, leading to inferences about their origin and function (Goyal et al, 2022). Likewise, ginseng, an herbal supplement widely grown and used in Korea, China, and Japan, is rich in biological properties that significantly prolong lifespan, increase libido, suppress cardiovascular diseases, and many more (Yue et al, 2007).…”
Section: Ginseng In Veterinary Practice: Benefits and Considerationsmentioning
confidence: 99%
“…5 This extract is believed to possess various bioactive components like flavonoids, alkaloids, saponins, and phenolic compounds which are thought to contribute to its nephroprotective effect. 6,7 C. paradisi, commonly known as grapefruit, is a citrus fruit belonging to the family Rutaceae Practitioners of conventional medicine often use it to address including kidney diseases. Several studies have reported anti-inflammation, antioxidant, and antimicrobial actions of the hydroalcoholic extract of C. paradisi.…”
mentioning
confidence: 99%